2022
DOI: 10.3390/fractalfract6080445
|View full text |Cite
|
Sign up to set email alerts
|

On the Numerical Approximation of Mobile-Immobile Advection-Dispersion Model of Fractional Order Arising from Solute Transport in Porous Media

Abstract: The fractional mobile/immobile solute transport model has applications in a wide range of phenomena such as ocean acoustic propagation and heat diffusion. The local radial basis functions (RBFs) method have been applied to many physical and engineering problems because of its simplicity in implementation and its superiority in solving different real-world problems easily. In this article, we propose an efficient local RBFs method coupled with Laplace transform (LT) for approximating the solution of fractional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…Solute transport in porous media is governed by three main mechanisms: advection, diffusion, and dispersion [39][40][41]. The mathematical formulation of the advection-diffusiondispersion equation is explained briefly here in terms of implementing the flow and transport factors that affect the transport process.…”
Section: Underlying Physicsmentioning
confidence: 99%
“…Solute transport in porous media is governed by three main mechanisms: advection, diffusion, and dispersion [39][40][41]. The mathematical formulation of the advection-diffusiondispersion equation is explained briefly here in terms of implementing the flow and transport factors that affect the transport process.…”
Section: Underlying Physicsmentioning
confidence: 99%
“…Many scholars [81,82] have found that the conventional CDE model falls short in explaining the occurrence of early breakthrough and tailing phenomena in the transport of solutes in heterogeneous media. Some scholars [83,84] have discovered that even in soil columns or troughs that are uniformly filled indoors, irregular solute transport phenomena may occur. Furthermore, the CDE model is limited in capturing variations in pollutant concentrations only within the upper layers of soil, and falls short in providing satisfactory simulation results for deeper layers [85].…”
Section: Application and Progress In The Assessment Of Process-based ...mentioning
confidence: 99%